Analisis penerapan PPh final 1% atas penjualan rumah subsidi: Studi kasus pada PT. Bumi Mapanget Asri Manado - Lamadi, Pricilia Virginia; Elim, Inggriani; Wangkar, Anneke (Riset Akuntansi dan Portofolio Investasi, 2025)
This study analyzes the implementation of the Final Income Tax (PPh Final) Article 4 Paragraph (2) at a rate of 1% on the sale of subsidized housing at PT Bumi Mapanget Asri Manado. A case study qualitative approach was employed, using interviews and document analysis as data collection techniques. The results reveal that the mechanism of tax withholding and deposit has been carried out in accordance with Government Regulation No. 34 of 2016 and Minister of Finance Regulation No. 81 of 2024. However, the reporting process was adjusted based on the instructions from the Account Representative of the Manado Primary Tax Office. Administrative challenges were identified, particularly in the delay of certificate separation and the issuance of the Tax Object Number (NOP), which affected the timeliness of accounting recognition of transactions. This study contributes to the literature on property taxation and provides practical recommendations for developers in improving tax compliance and administrative efficiency.